Prevalence of Hypertrophic Cardiomyopathy in Fetuses of Mothers with Gestational Diabetes before Initiating Treatment - Carolina Rossi Palmieri; Mona Adalgisa Simões; Jean Carl Silva; Anelise Darabas dos Santos; Mariana Ribeiro e Silva; Bruna Ferreira (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
ABSTRACT Objective: To evaluate the prevalence of hypertrophic cardiomyopathy (HCM) in fetuses of pregnant women with gestational diabetes mellitus (GDM) in the beginning of the treatment. Methods: A cross-sectional study was performed between July 1, 2013, and Decem-ber 20, 2013, in a public maternity clinic in southern Brazil. The subjects were 63 fetuses of mothers with gestational diabetes, with a single pregnancy and no other associated pathologies. We diagnosed HCM through a fetal echocardiography before treatment and evaluated the maternal and fetal characteristics. Results: The average age of the pregnant women was 32.32 (±6.2) years, and the average gestational age at the time of the evaluation was 30.59 (±2.27) weeks. The interventricular septum thickness showed a standard deviation of more than two in 50.8% of the fetuses (95% confidence interval [95%CI]: 38.1-63.5%). The left ventricular wall thickness showed a standard deviation of more than 2 in 13 (20.6%) fetuses (95%CI: 11.1-30.2%). The HCM was confirmed in 54% of the fetuses (95%CI: 41.3-65.1%). The fetal abdominal circumference was normal in 46 (73%) fetuses, and 50% of these fetuses had HCM. Conclusion: The prevalence of hypertrophic cardiomyopathy in fetuses of pregnant women with GDM before treatment was of 54% (95%CI: 41.3-65.1%).